2010
DOI: 10.1007/s00705-010-0883-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis E virus among swine and humans in two different ethnic communities in Indonesia

Abstract: The purpose of this study was to investigate the prevalence of hepatitis E virus (HEV) infection in swine and humans in different environments in Java and Bali, Indonesia. The prevalence of anti-HEV antibodies in people over 20 years old living in communities in Bali was significantly higher than that in Java. While 68.8% and 90.0% of swine in Bali were anti-HEV positive at 1 and 2 months of age, respectively, swine in Java were at significantly lower risk of HEV infection by the age of 2 months. Our present d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…After combining the Yogyakarta and Tulungagung samples as all from Java, the prevalence of anti‐HEV antibody seropositivity in 1‐ and 2‐month‐old swine was found to be 5.2% (1/19) and 43.3% (13/30), respectively. Eleven of 16 (68.8%) 1‐month‐old swine and 18/20 (90%) 2‐month‐old swine in Bali were positive for anti‐HEV antibodies . There were significant differences between Java and Bali in the rates of anti‐HEV antibody seropositivity, seropositivity in the 1‐ and 2‐month‐old swine being higher in Bali than in Java ( P < 0.001 and P =0.01).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…After combining the Yogyakarta and Tulungagung samples as all from Java, the prevalence of anti‐HEV antibody seropositivity in 1‐ and 2‐month‐old swine was found to be 5.2% (1/19) and 43.3% (13/30), respectively. Eleven of 16 (68.8%) 1‐month‐old swine and 18/20 (90%) 2‐month‐old swine in Bali were positive for anti‐HEV antibodies . There were significant differences between Java and Bali in the rates of anti‐HEV antibody seropositivity, seropositivity in the 1‐ and 2‐month‐old swine being higher in Bali than in Java ( P < 0.001 and P =0.01).…”
Section: Resultsmentioning
confidence: 93%
“…The total prevalence of anti‐HEV in humans in Bali was 11.6%. Of 64 workers and 135 local residents from Bali, 12 (18.8%) and 11 (8.1%), respectively, were anti‐HEV antibody positive . The overall prevalence of anti‐HEV antibody seropositivity in Bali was significantly higher than that in Java ( P = 0.015).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…As shown in Figure , a total of 1987 studies were initially found in CNKI, PubMed and OVID, in which 234 studies were potentially related to our study objectives and had a full text retrieved. Subsequently, 204 studies were excluded with reasons listed in Figure , and two studies were added in an updated search, yielding 32 studies for the meta‐analysis (Bouwknegt et al, ; Caruso et al, ; De Sabato et al, ; Drobeniuc et al, ; Engle, Yu, Emerson, Meng, & Purcell, ; Galiana, Fernandez‐Barredo, Garcia, Gomez, & Perez‐Gracia, ; Hinjoy et al, ; Hongwei, ; Jiang, Zheng, & Shijuan, ; Kang et al, ; Krumbholz et al, ; Lange et al, ; Lee et al, ; Liang et al, ; Liu et al, ; Love, Bjornsdottir, Olafsson, & Bjornsson, ; Lu et al, ; Masia et al, ; Meng et al, ; Nong, Li, & Yi, ; Olsen, Axelsson‐Olsson, Thelin, & Weiland, ; Silva et al, ; Traore et al, ; Utsumi et al, ; Vivek & Kang, ; Wu, Liao, Wang, Lou, & Wenzhong, ; Wu, Xie, et al, ; Yan et al, ; Yu et al, ; Zheng et al, ). Of the included studies, 24 were published in English and eight in Chinese.…”
Section: Resultsmentioning
confidence: 99%